Implementation of the Art of Al-Quran Reading Learning to Improve Al-Quran Reading Skills in Students of Baitul Mukminin Islamic Boarding School, Pardang City - Muhammad Aldian Syah; Martin Kustati; Rezki Amelia; Gusmirawati (al-Afkar, Journal For Islamic Studies, 2025)
This research aims to evaluate the implementation of learning the art of reading the Al-Quran and its impact on the ability to read the Al-Quran among Koran teachers in Padang City. The method used is qualitative research with a case study approach. Data was collected through in-depth interviews, direct observation, and analysis of documents related to the learning program. The findings show that the application of reading arts techniques, such as the use of appropriate tajwid, correct makhraj, and attractive intonation, significantly improves the teachers' Al-Quran reading skills. Apart from that, this learning also increases teacher confidence and motivation in teaching, and strengthens the relationship between teachers and students. This research concludes that the integration of arts in Al-Quran learning is an effective strategy for improving the quality of reading and teaching among Koran teachers.